Analisis Peringkat Kredit Korporasi Non-Keuangan di Indonesia Ditinjau Dari Model dan Indikator Risiko Kredit Berbasis Data Akuntansi dan Data Pasar Periode 2013 - 2022 - Tanukusuma, Reinard; Rizkianto, Eko (UI Scholars Hub, 2025)
This research entails an examination of credit risk assessment (credit rating) with respect to credit risk assessment models utilizing accounting data and market data for non-financial corporations in Indonesia between the years 2013 and 2022. The sample comprises credit rating values of 20 companies listed on the Indonesia Stock Exchange and included in the IDX 80 index, possessing credit ratings from PEFINDO over a ten-year period from 2013 to 2022. Panel data analysis is conducted, employing the multiple linear regression method. The findings of this study reveal that the accounting data-based model demonstrates the significance of liquidity, capital structure, and interest payment ability indicators, while the market data-driven model highlights the influence of equity volatility and market multiples indicators in respect on credit ratings. Moreover, the study concludes that the combined model incorporating accounting data-based and market data-driven models provides a more comprehensive and holistic explanation of credit ratings.